Study of Antimicrobial Resistance Bacterial Genes in Infective Endocarditis - Noorjan Abdul Hameed Namuq; Asma S.A. Karomi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background:Endocarditis is a dangerous inflammation of the heart’s inner lining, known as the endocardium, which encompasses the chambers and valves. Endocarditis is typically induced by an infection. Bacteria, fungus, or other pathogens enter the bloodstream and adhere to compromised regions of the heart. In the absence of prompt intervention, endocarditis can impair or obliterate the heart valves. Method: 230 Blood sample were collected from Infective Endocarditis patients, blood culture used for bacterial growth and identification of bacterial species were completed by microscopic examination, culture characteristics, and biochemical tests, and the use of the Vitek 2 diagnostic system for final identification of the isolated bacteria. Biofilm were detected by microtiter plate and Congo agar methods and Ethidium bromide used for efflux pumps dertection, icaAand norA genes for Staphylococcus spp. and mexR gene for Pseudomonas aeruginosa were detected by PCR. Results: 51 positive culture for bacterial growth, 18 were staph. aureus bacteria and 7 were P. aeruginosa. Staphylococci were the most biofilm forming (9) positive by the CRA method and (8) moderately forming by the MTP method, while P. aeruginosa were the least biofilm forming by both methods (1),(1). Staphylococcus showed positive results at various concentrations of the dye, while the bacteria Pseudomonas aeruginosa were positive for the efflux pumps only at concentrations (1,2) of the dye. icaA gene were found in 21.4% and 25% of S. aureus and S. epidermidis respectively, while norA gene found in 7.1% of S. aureus and mexR gene in 25% of P.aeruginosa. Conclusion: Staph. aureus and P. aeruginosa have many virulence factors genes that contributed in the infective Endocarditis infection and they were resistant to many antibiotics due to these genes.